2019
DOI: 10.1111/tra.12673
|View full text |Cite
|
Sign up to set email alerts
|

The roles of Centrin 2 and Dynein Light Chain 8a in apical secretory organelles discharge of Toxoplasma gondii

Abstract: To efficiently enter host cells, apicomplexan parasites such as Toxoplasma gondii rely on an apical complex composed of tubulin‐based structures as well as two sets of secretory organelles named micronemes and rhoptries. The trafficking and docking of these organelles to the apical pole of the parasite is crucial for the discharge of their contents. Here, we describe two proteins typically associated with microtubules, Centrin 2 (CEN2) and Dynein Light Chain 8a (DLC8a), that are required for efficient host cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 67 publications
1
46
0
Order By: Relevance
“…This differential distribution of TgCEN2 points to versatile functions of TgCEN2 in the four distinct structures. Experimental evidence based on gradual depletion and knockdown of TgCEN2 revealed that this protein is involved in several Ca 2+ -mediated processes, namely microneme secretion, motility, host cell attachment, invasion, and egress [21]. In addition, these analyses also indicate that the depletion of TgCEN2 from the four locations follows different kinetics, first from the pre-conoidal rings and peripheral annuli, leading to major invasion defects, and later from basal complex and centrioles, resulting in replication deficiency [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This differential distribution of TgCEN2 points to versatile functions of TgCEN2 in the four distinct structures. Experimental evidence based on gradual depletion and knockdown of TgCEN2 revealed that this protein is involved in several Ca 2+ -mediated processes, namely microneme secretion, motility, host cell attachment, invasion, and egress [21]. In addition, these analyses also indicate that the depletion of TgCEN2 from the four locations follows different kinetics, first from the pre-conoidal rings and peripheral annuli, leading to major invasion defects, and later from basal complex and centrioles, resulting in replication deficiency [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence based on gradual depletion and knockdown of TgCEN2 revealed that this protein is involved in several Ca 2+ -mediated processes, namely microneme secretion, motility, host cell attachment, invasion, and egress [21]. In addition, these analyses also indicate that the depletion of TgCEN2 from the four locations follows different kinetics, first from the pre-conoidal rings and peripheral annuli, leading to major invasion defects, and later from basal complex and centrioles, resulting in replication deficiency [21,22]. In this scenario, identifying the physical interactors of TgCEN2 and characterizing the magnitude of the reciprocal interactions between Ca 2+ , TgCEN2 and TgCEN2-binding targets will be crucial to unravel the exact Ca 2+ -sensing properties, mode of action and biological function of this centrin isoform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In apicomplexan parasites, the cilium was likely adapted to form the organizing core of the "apical complex" of cytoskeletal structures and secretory organelles for which the phylum is named (Figure 1; de Leon et al, 2013). The protein components of the apical complex include orthologs of cilium-associated proteins including centrins (Hu et al, 2006;Lentini et al, 2019), a SAS6 cartwheel protein (de Leon et al, 2013;Lévêque et al, 2016), an associated rootlet fiber (Francia et al, 2012), and a distributed microtubule-organizing center called the apical polar ring (Leung et al, 2017). During the asexual stage, Apicomplexa such as Toxoplasma have a specialized cilium-like structure called the conoid, and typical motile flagella grow at this site during the sexual stage (Francia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We identify four new annuli proteins, AAP2, AAP3, AAP5, and the AAMT. AAP4 has been previously detected in BioID data sets of the alveolar suture component ISC4 (Chen et al, 2016), of the conoid (Long et al, 2017a) and a protein above the conoid, SAS6L (Lentini et al, 2019). Lentini et al further co-localized AAP4 with Centrin2 and describe a relationship between Centrin2 knockdown and AAP4 abundance in the parasite (Lentini et al, 2019).…”
Section: Discussionmentioning
confidence: 96%